Functional Characterization of BrF3'H, Which Determines the Typical Flavonoid Profile of Purple Chinese Cabbage - Park, Sangkyu; Lee, Hyo; Min, Myung Ki; Ha, Jihee; Song, Jaeeun; Lim, Chan Ju; Oh, Jinpyo; Lee, Saet Buyl; Lee, Jong-Yeol; Kim, Beom-Gi (Frontiers in Plant Science, 2021)
Flavonols and anthocyanins are the two major classes of flavonoids in Brassica rapa. To elucidate the flavonoid biosynthetic pathway in Chinese cabbage (B. rapa L. subsp. pekinensis), we analyzed flavonoid contents in two varieties of Chinese cabbage with normal green (5546) and purple (8267) leaves. The 8267 variety accumulates significantly higher levels of quercetin, isorhamnetin, and cyanidin than the 5546 variety, indicating that 3′-dihydroxylated flavonoids are more prevalent in the purple than in the green variety. Gene expression analysis showed that the expression patterns of most phenylpropanoid pathway genes did not correspond to the flavonoid accumulation patterns in 5546 and 8267 varieties, except for BrPAL1.2 while most early and late flavonoid biosynthetic genes are highly expressed in 8267 variety. In particular, the flavanone 3′-hydroxylase BrF3′H (Bra009312) is expressed almost exclusively in 8267. We isolated the coding sequences of BrF3′H from the two varieties and found that both sequences encode identical amino acid sequences and are highly conserved with F3'H genes from other species. An in vitro enzymatic assay demonstrated that the recombinant BrF3′H protein catalyzes the 3′-hydroxylation of a wide range of 4′-hydroxylated flavonoid substrates. Kinetic analysis showed that kaempferol is the most preferred substrate and dihydrokaempferol (DHK) is the poorest substrate for recombinant BrF3′H among those tested. Transient expression of BrF3′H in Nicotiana benthamiana followed by infiltration of naringenin and DHK as substrates resulted in eriodictyol and quercetin production in the infiltrated leaves, demonstrating the functionality of BrF3′H in planta. As the first functional characterization of BrF3′H, our study provides insight into the molecular mechanism underlying purple coloration in Chinese cabbage.